Медіафілософія у сучасному інформаційному просторі - Андрос, А. М.; Лутай, В. О.; Кравченко, С. О. (ХНУРЕ, 2019)
The article attempts to determine the role and significance of media philosophy in the modern media space, to establish interconnection with such concepts as media culture and media literacy. Today, users of media resources are processing large volume of media text, and therefore may require some knowledge of media philosophy.